INFLUENCE OF DUAL PROCEDURAL JUSTICE FROM TWO ORGANIZATION TO JOB SATISFACTION, ORGANIZATIONAL COMMITMENT AND PROSOCIAL BEHAVIOR ON OUTSOURCE SERVICE PROVIDERS - Trenggono Sutiyoso (Universitas Trisakti, 2010)
The purpose of this study was to know the influence of procedural justice from two organizations, that were service’s and customer’s organizations, to employee’s job satisfaction and organizational commitment to each Organization. The research also test the influence of job satisfaction and dual organizational commitment of outsource employee to their prosocial behavior. Data are gathered through a survey among 286 employees of outsource service providers from 11 organizations which were worked for 6 customer’s organization on mining sector. The model was tested using structural equation modelling (SEM). The results indicated that both procedural justice from the organizations influenced the employee job satisfaction, procedural justice and job satisfaction influenced the organizational commitment to each organization and job satisfaction also influence prosocial behavior inrole and extrarole. Organizational commitment from both organization was not significant influencing the employee prosocial behavior in-role and extra-role. Practical implication of the findings, procedural justice from customer’s organization was an importantfactor to improve the prosocial behavior which was mediated by employee’s job satisfaction. The finding also implies that service provider has not any influence to the employee’s prosocialbehavior, that mean the service provider were only providing workforces to customer and has limited interaction with their employee